2021
DOI: 10.3390/s21154968
|View full text |Cite
|
Sign up to set email alerts
|

Printed Circuit Board Defect Detection Using Deep Learning via A Skip-Connected Convolutional Autoencoder

Abstract: As technology evolves, more components are integrated into printed circuit boards (PCBs) and the PCB layout increases. Because small defects on signal trace can cause significant damage to the system, PCB surface inspection is one of the most important quality control processes. Owing to the limitations of manual inspection, significant efforts have been made to automate the inspection by utilizing high resolution CCD or CMOS sensors. Despite the advanced sensor technology, setting the pass/fail criteria based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Several works have investigated the use of skip connections in AEs for tasks such as image denoising [22], [23] and audio separation [24]. Our work differs from current works on overcomplete and skip-AEs for anomaly detection [12]- [15], [25]: we have investigated a wider range of non-bottlenecked AEs, in which overcomplete or skip-AEs are only one type, and experimented with more datasets.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have investigated the use of skip connections in AEs for tasks such as image denoising [22], [23] and audio separation [24]. Our work differs from current works on overcomplete and skip-AEs for anomaly detection [12]- [15], [25]: we have investigated a wider range of non-bottlenecked AEs, in which overcomplete or skip-AEs are only one type, and experimented with more datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Skip connections allow a better flow of information in NNs with many layers, leading to a smoother loss landscape [41] and easier optimisation, without additional computational complexity [42]. Recent works [14], [15], [25] have reported that AEs with skip connections outperform those without on image anomaly detection. In preventing the skip-AEs from learning the identity function, Collin et al [14] and Baur et al [15] have implemented a denoising scheme and a dropout mechanism, respectively.…”
Section: A Bayesian Autoencodersmentioning
confidence: 99%
“…Skip connections allow a better flow of information in NNs with many layers, leading to a smoother loss landscape [17] and easier optimisation, without additional computational complexity [18]. Recent works [19,20,21] have reported that AEs with skip connections outperform those without on image anomaly detection. In preventing the skip-AEs from learning the identity function, Collin et al [20] and Baur et al [19] have implemented a denoising scheme and a dropout mechanism, respectively.…”
Section: A Undercompletementioning
confidence: 99%
“…Hu and Wang [ 15 ] used ResNet50 with a feature pyramid network as the backbone of feature extraction to better detect small defects on the PCB. Kim et al [ 16 ] proposed an advanced PCB inspection system based on skip connection convolutional autoencoders for the problem of setting pass/fail criteria for small fault samples. Ding et al [ 17 ] were inspired by the similarity measurement and proposed a multi-layer deep feature fusion method to calculate the similarity between the template and the defective circuit board.…”
Section: Introductionmentioning
confidence: 99%